Higher sowing density of pearl millet increases productivity and water use efficiency in high evaporative demand seasons - Pilloni, Raphaël; Faye, Aliou; Kakkera, Aparna; Kholova, Jana; Badji, Romiel; Faye, Coumba; Vadez, Vincent (Frontiers in Plant Science, 2022)
Pearl millet is the main subsistence crop for smallholder farmers systems where it is grown at low plant density (around 3 plants/m²). Intensifying pearl millet cultivation could boost productivity although it is unclear if water stress could become an issue. Indeed, increasing planting density would increase the leaf area and the related water budget. However, a denser canopy could also create a more favorable canopy microclimate to the benefit of the water use efficiency (WUE) of the crops. The first aim of this work was to test the yield response of popular pearl millet varieties to an increased density in different field locations (Senegal and India), and to assess possible genotypic variation in this response. The second aim was to measure the water use and the WUE of the crop in different densities, using lysimeters. The higher sowing density significantly increased yield in all genotypes when the trials were carried out in high evaporative demand conditions. There was no genotype x density interaction in these trials, suggesting no genotypic variation in the response to density increase. The high-density treatment also decreased the vapor pressure deficit (VPD) in the canopies, both in the field and in the lysimeter experiments. Although the higher density treatment increased water use, the resulting increase in biomass was proportionally higher, hence increasing WUE of the crops in all genotypes under high density. The increase in yield under high density was closely related to the increase in WUE, although this link was more tight in the high- than in the low evaporative demand seasons. This confirmed a strong environmental effect on the response to density of all the genotypes tested. Although they did not open a scope for breeding density tolerant cultivars, these results highlight the possibility to improve pearl millet yield by increasing the density, targeting specifically areas facing high evaporative demand.